Grammatical Terminology for the Teaching of African Languages at Tertiary Level - Msimang, C.T. (Lexikos, 2000)
Abstract: The article addresses the question Of the elaboration and modei'nisation of ,African languages to enable them to be used as language media for the teaching of African languages, particularly grammar. Whereas all institutions at tertiary level of education have undergone' a paradigm shift from teaching African languages in English and Afrikaans to teaching them in their own medium, the necessary terms to ensure efficiency in this process are lacking. Scholars therefore need to focus on tenn creation and thereafter standardization of the terminologies. Some flaws in the creation of African tenninologies in the past are highlighted and remedies suggested. It is recomme,nded that statutory bodies such as the Council for Higher Education (CHE) or the South African Qualifications Authority (SAQA), or academic bodies such as the African Languages Assodation of Southern Africa (ALASA) could be entrusted with the task of the standardization of these tenninologies.Keywords: AFRICAN LANGUAGES, LANGUAGE MEDIUM, GRAMMATICAL, TERMINOLOGY, TERM CREATION,. STANDARDIZATION Of TERMINOLOGY, TEACHING ATTERTIARY LEVELOpsomming: Grammatiese terminologie vir die onderrig vall Afrikatal~ optersiere vlak. Die artikel behandeldie vraag oor die uitbouing en,modernisering van Afrikataleom hulle in staat te stel om as taalmedia gebruik te word in die onderrig van Afrik3tale, veral taalkunde.'Waar aile inrigtings or tersiere opvoedkundige vlak 'n paradigmaverskuiwing ondergaanhet vanaf die onderrig van Afrikatale in Engels en Afrikaans na die onderrig daarvan in hul eiemedium, ontbreek die'nodige tenne' om doeltreffendheid in hierdie proses te verseker. Geleerdesmoet hulle daarom toespits op tennskepping en da~rna op die standaardisering van die tenninologiee.Sommige gebreke in die skepping van die Afrikataaltenninologiee in die verlede word beligen regstellings voorgestel. Daar word aanbeveel dat statutêre Iiggame soos die Raad op Heer Onderwys(RHO) of die Suid-Afrikaanse Kwalifikasieowerheid (SAKO), of akademiese verenigingssoos die Afrikatale-Vereniging van Suider-Afrika (AVSA) met die taak van die standaardisering van hierdie terrninologiee toevertrou word.Keywords: AFRIKATALE, TAALMEDIUM, GRAMMATIKA TERMINOLOGIE, TERMSKEPPING,TERMINOLOGIESTANDAARDISERlNG, ONDERRIG OP TERSIÊRE VLAK.